2021
DOI: 10.1097/nmd.0000000000001312
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Climate Change on Human Trafficking

Abstract: Climate change is a threat to the public health with wide-reaching impacts that are becoming more studied and recognized. An aspect of climate change that has not yet gained adequate scholarly attention is its potential impact on human trafficking. We review the potential impact of climate change on risk factors to human trafficking including poverty, gender inequality, political instability, migration or forced displacement, and weather disasters. We conclude that climate change is a crucially important consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…root causes and risk factors) that increase vulnerability and varied pathways to being trafficked is critical for effective public health prevention and intervention work [ 20 , 21 ]. Furthermore, major societal stressors, such as an economic crisis [ 2 ], disease outbreak [ 22 ], or climate change-related natural disasters [ 23 ], may exacerbate vulnerability to trafficking by increasing risk factors and disrupting existing sources of support. Significant research challenges exist given the complex phenomenon of modern slavery, including human trafficking’s clandestine nature, association with various economies [ 24 ], lack of reliable data and statistics [ 25 , 26 ], and fragmented information (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…root causes and risk factors) that increase vulnerability and varied pathways to being trafficked is critical for effective public health prevention and intervention work [ 20 , 21 ]. Furthermore, major societal stressors, such as an economic crisis [ 2 ], disease outbreak [ 22 ], or climate change-related natural disasters [ 23 ], may exacerbate vulnerability to trafficking by increasing risk factors and disrupting existing sources of support. Significant research challenges exist given the complex phenomenon of modern slavery, including human trafficking’s clandestine nature, association with various economies [ 24 ], lack of reliable data and statistics [ 25 , 26 ], and fragmented information (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Women often see Saudi Arabia as a place offering solace from domestic violence. Migration drivers vary by context; for instance, Sheu et al (2021) identified common push factors in certain countries, including violence, gender inequality, political corruption, environmental degradation, climate change, and lack of access to healthcare and education. Among the push factors discussed by Sheu et al (2021), gender inequality stands out as particularly relevant to Ugandan domestic workers, sometimes leading to domestic violence.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Migration drivers vary by context; for instance, Sheu et al (2021) identified common push factors in certain countries, including violence, gender inequality, political corruption, environmental degradation, climate change, and lack of access to healthcare and education. Among the push factors discussed by Sheu et al (2021), gender inequality stands out as particularly relevant to Ugandan domestic workers, sometimes leading to domestic violence. Fernandez (2011) noted that many young Ethiopian women are migrating to Arab Gulf countries for domestic work despite the risks, such as low pay, physical violence, and harassment by some employers in Saudi Arabia.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Climate change can have a compounding effect on human trafficking (Hoogesteyn et al 2024), as it has both short and long term impacts on economic development and physical and social infrastructure. It harms the livelihoods of households, which increases the numbers of trafficking-vulnerable individuals (Bharadwaj et al 2022), especially around the tropics (Molinari 2017;Sheu et al 2021). Shocks from climate disasters in trafficking destinations can also incentivize trafficking flows by creating illicit economic opportunities (Worsnop and Vogel 2024).…”
Section: Introductionmentioning
confidence: 99%